2020
DOI: 10.1186/s13073-020-0718-7
|View full text |Cite
|
Sign up to set email alerts
|

The pan-cancer landscape of prognostic germline variants in 10,582 patients

Abstract: Background: While clinical factors such as age, grade, stage, and histological subtype provide physicians with information about patient prognosis, genomic data can further improve these predictions. Previous studies have shown that germline variants in known cancer driver genes are predictive of patient outcome, but no study has systematically analyzed multiple cancers in an unbiased way to identify genetic loci that can improve patient outcome predictions made using clinical factors. Methods: We analyzed seq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 64 publications
1
25
0
Order By: Relevance
“…We next sought to characterize the somatic events associated with GVITMB. Several studies have suggested that germline variants influence somatic events ( Carter et al., 2017 ; Chatrath et al., 2019 , 2020 ; Chirita-Emandi et al., 2020 ). We found that patients with GVITMB in mismatch repair genes exhibited enrichment of mutational signatures associated with mismatch repair gene dysfunction, suggesting exome-wide evidence of the dysfunction of these genes ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next sought to characterize the somatic events associated with GVITMB. Several studies have suggested that germline variants influence somatic events ( Carter et al., 2017 ; Chatrath et al., 2019 , 2020 ; Chirita-Emandi et al., 2020 ). We found that patients with GVITMB in mismatch repair genes exhibited enrichment of mutational signatures associated with mismatch repair gene dysfunction, suggesting exome-wide evidence of the dysfunction of these genes ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although patients with pathogenic germline variants are often screened more aggressively for cancer, clinical guidelines for these patients have only changed in a few circumstances ( Le et al., 2017 ; Lindor et al., 2006 ). We had previously identified common germline variants associated with differences in patient outcome across a multitude of cancers, suggesting that germline variation contributes not only to cancer risk but also to tumor progression ( Chatrath et al., 2019 , 2020 ). In this study, we have identified pathogenic germline variants associated with TMB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most variants demonstrate a modest increase in risk [ 5 ], the combined effects of multiple SNPs are potentially useful in population-based cancer risk stratification and prevention programs [ 13 , 14 ]. Likewise, GWAS studies have also identified SNPs associated with response to chemotherapy [ 15 ], treatment-related toxicity [ 16 ], and clinical outcomes in cancer patients [ [17] , [18] , [19] ]. Therefore, identifying SNPs and other genetic alterations that correlate with clinical outcome may provide novel insight into the pathobiology and management of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, germline variants have been known to influence the somatic mutational landscape of cancer tumours by changing the structures of genes and amino acid sequences, affecting the distribution of somatic mutations and causing global enrichment of mutations [ 8 ]. So far, many studies have revealed the direct effect of germline variants or their interaction with somatic mutations in predicting the outcome of patient treatments or sensitivity of cancer cell lines in high-throughput drug screens (HTSs) [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%